2014
DOI: 10.1007/s12595-014-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

Season-Induced Changes in the Liver Cells and Ovarian Tissues During Growth, Maturation, Spawning and Post-spawning Phases in Spiny Eel Mastacembelus armatus (Lacepède, 1800)

Abstract: Cytological status of hepatocytes in respect to seasons influencing ovarian activities has been studied in Mastacembelus armatus (Hamilton). Histologically, the hepatocyte of female liver was provided with distinct nucleus and basophilic cytoplasmic granules. In M. armatus different germ line cells were recognized on the basis of size and histoarchitecture of the cells. By examining seasonal changes in relation to hepatocytes and ovary, it was found that during growth and maturation phases the density of cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Seasonal variations in ovarian and testicular morphology and levels of sex steroids in C. batrachus are in agreement with the earlier reports on seasonally breeding teleost fishes (Chakrabarti and Chatterjee, 2014;Schulz et al, 2010;Singh et al, 2008) and also recently reported for the catfish, C.batrachus (Priyadarshini Lal, 2018; Singh nee Priyadarshini and Lal, 2018). However, increase in serum17β-estradiol during the later part of laterecrudescence phase (June) could be because of its more release from the ovary than its production.…”
Section: Discussionsupporting
confidence: 92%
“…Seasonal variations in ovarian and testicular morphology and levels of sex steroids in C. batrachus are in agreement with the earlier reports on seasonally breeding teleost fishes (Chakrabarti and Chatterjee, 2014;Schulz et al, 2010;Singh et al, 2008) and also recently reported for the catfish, C.batrachus (Priyadarshini Lal, 2018; Singh nee Priyadarshini and Lal, 2018). However, increase in serum17β-estradiol during the later part of laterecrudescence phase (June) could be because of its more release from the ovary than its production.…”
Section: Discussionsupporting
confidence: 92%